The Relation between Healing Time and Patient’s Characteristic in the Treatment of Common Warts with the Application of 80% Phenol Solution - Dina Arwina Dalimunthe; Remenda Siregar; Chairiyah Tanjung (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Common warts are skin diseases which caused by human papilloma virus (HPV) infection. There are many modalities treatment for common warts, one of them is the application of 80% phenol solution that is classified as topical treatment. Purpose: To determine the healing time in treatment of common warts with the application of 80% phenol solution and it’s relation with age and sex of the patients. Methods: Open clinical trial was done at Dr. Pirngadi General Hospital Medan and H. Adam Malik General Hospital Medan from February to June 2013 on 17 patients with common warts. The application of 80% phenol solution was performed on patients and continued every week until complete regression, maximum of 6 weeks. Follow up was carried out every week for six weeks to observe healing time. Data were analyzed by Mann-Whitney test with α=0,05. Result: After six weeks, 11 patients (64,7%) were healed. Healing time was varied from 3 to 6 weeks, mostly 4 weeks (45,4%). Result of Mann-Whitney test showed statistically significant relationship between healing time and age (p=0,027) whereas the healing time were faster on patient 14 years and older, and no relation between healing time and sex (p=0,422). Conclusion: There was relation between healing time in application of 80% phenol solution with age in treatment of common warts and no relation with the sex of the patient.Key words: common warts, 80% phenol solution.